Abundance and Spatial Distribution of Commerson’s Dolphin (Cephalorhynchus commersonii) at a Breeding Site: Ría Deseado, Patagonia, Argentina - Righi, Carina F. (2013)
Abundance and spatial distribution of the Commerson’s dolphin (Cephalorhynchus commersonii) during spring and summer 2002-2004 and fall/winter 2003 were estimated in the estuary Ría Deseado, Patagonia, Argentina. To estimate the abundance, photo-identification and mark-recapture (positive method) were combined. Distribution of dolphins within the estuary was studied, and their locations were recorded using a GPS to perform a Kernel Density Analysis. Adult abundance was higher during spring (34 and 35 individuals in 2002 and 2003, respectively) and decreased during fall (7 individuals) and winter (16 individuals). Sightings of 132 adults during winter, spring, and summer (n = 12, n = 76, and n = 44, respectively) and 14 calves during spring and summer (n = 4 and n = 10, respectively) were recorded; mean school size was 2.0 ± 1.2. Distribution and abundance varied seasonally. During spring, dolphins were more equally distributed through the estuary than during summer when calves and adults remained mainly inside the estuary. The presence of dolphins year-round suggested that the inhabitants are residents of the estuary. This study offers new information on the ecology of the Commerson’s dolphin and confirms Ría Deseado as a breeding site for this species.